Soy-Ipoghurt as an antidiabetic on hiperglicemic animal modelling Rattus norvegicus - I Putu Dedy Arjita; Dhika Juliana Sukmana; Hardani Hardani; Diani Sri Hidayati; I Putu Bayu Agus Saputra (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2023)
Treatment of Diabetes Mellitus (DM) is generally through optimizing a balanced diet. Soybeans and sweet potatoes have good antioxidants and can be developed as healthy foods for people with diabetes. Soybeans and sweet potatoes are processed into Soy-yoghurt. This study aims to determine the potential of soy yogurt as an antidiabetic in experimental animals, Rattus norvegicus induced by hyperglycemia, using Streptozotocin. This study used a experiment design with a total of 40 experimental animals. The research was conducted at the Medica Farma Husada Polytechnic Laboratory, Mataram, in 2022. The experimental animals that Streptozotocin (STZ) induced were then given Soy-yogurt orally at 3 ml and 3.5 ml doses. Experimental animals' Fasting Blood Glucose (FBG) levels were measured weekly using a Glucometer, while body weight (BW) was measured every three days. The results obtained were then analyzed statistically using the ANOVA test. The test results showed that there was a significant difference in blood sugar levels (p<0,05) in fasting given soy but no difference in BW (p>0,05). This study concludes that the provision of soybeans can affect the level of FBG of the experimental animals but does not affect the BW of the experimental animals.